Analysis of Factors Affecting Tax Aggressiveness in Public Companies - Loso Judijanto (Nomico, 2025)
This study analyses the factors that influence tax aggressiveness in public companies by examining the interaction between company financial characteristics, governance structure, and institutional environment. Using a quantitative panel data research design, this study evaluates 84 firm-year observations from Indonesia and Malaysia using fixed effects and random effects models to test how leverage, profitability, company size, ownership concentration, and governance quality influence tax aggressiveness as measured by cash effective tax rate and book-tax differences. The findings show that higher leverage and profitability increase tax aggressiveness, while greater board independence and better audit quality decrease it. Institutional factors such as regulatory enforcement, legal clarity, and audit intensity moderate corporate behaviour and shape the level of tax aggressiveness. The results of the study reveal that tax aggressiveness is not driven by a single variable, but is the result of a combination of financial incentives and institutional opportunities. Companies operating in a weak regulatory environment exhibit higher tax aggressiveness, confirming the role of institutional quality in shaping compliance. This study concludes that reducing tax aggressiveness requires comprehensive reforms that integrate the strengthening of corporate governance with improvements in law enforcement and regulatory clarity. These findings contribute by offering a multidimensional analysis that combines internal and external determinants of tax behaviour